Inversor de frequência - Dal Moro, Marcos (2019)
With the advancement of technology in recent years, many industries ranging from communication to multi-segment productivity growth have grown to increase the productivity and profitability of various areas of the economy around the world. The agribusiness sector has significantly increased its production and profitability thanks to the facilities that technology has brought to rural properties. Companies have increasingly sought to develop products with the highest performance and that are capable of promoting increased production without increasing the area used. The aim of the study is to discuss the development of a system capable of driving threephase induction motors up to 2HP, for applications that have loads with quadratic torque requirements, such as fans. The project aims to implement a frequency inverter with singlephase input and three-phase output of 220V programmable frequency variation depending on the available starting and stopping ramps. This project also has protection system s for input and overvoltage, over current output and leakage from current to earth. The system will be activated with user interface via terminals and programming buttons or even by an external network communication system